Evaluation of EGFR mutation status in cytology specimens: An institutional experience. Issue 4 (18th November 2011) - Aisner, D. L.; Deshpande, C.; Baloch, Z.; Watt, C. D.; Litzky, L. A.; Malhotra, B.; Sepulveda, A. R.; Langer, C.; Evans, T.; Van Deerlin, V. M.
Abstract Epidermal growth factor receptor (EGFR) mutation status has been shown to predict response to anti‐EGFR tyrosine kinase inhibitors in non‐small cell lung cancer (NSCLC). In patients with advanced‐stage NSCLC, evaluation of mutational status is increasingly requested on biopsy or fine‐needle aspiration specimens, which often have limited material. There are limited data on the suitability of cytology cell blocks (CB) for EGFR mutation testing. In this study, we report our institutional experience with cytology cell block material for EGFR mutation testing. We retrospectively reviewed EGFR mutation analyses performed on 234 surgical (SP) and cytology (CB) from October 2007 to May 2010. One hundred ninety‐two SP specimens and 42 CB specimens were evaluated for EGFR mutation. CB specimens were evaluated for overall specimen size based on aggregate cellularity in comparison to small biopsy specimens, and percent tumor. Of the 192 SP and 42 CB specimens, 31 (16.1%) and 11 (26.2%) were positive for EGFR mutation, respectively; there does not appear to be an association between mutation detection rate and the source of the specimen (P = 0.124). Limited DNA was obtained from 70.0% (29/42), including 81.8% (9/11) of those which were mutation positive. Additionally, 45.4% (5/11) of mutation positive specimens had extremely low DNA yields. Although 16.6% (7/42) of CB specimens had <10% tumor, all 11 mutation positive CB cases had >10% tumor. These data indicate that CB specimens provide an alternative source for molecular evaluation of NSCLC, and that tumor percentage may be more important than specimen size and/or DNA yield in determining the suitability of these specimens for testing. Diagn. Cytopathol. 2013;41:316–323. © 2011 Wiley Periodicals, Inc.